Presenting new method on renovation of the Islamic cities - Joni, Raheleh Akbari; Utaberta, Nangkula; Mohd Rasdi, Mohd Tajuddin; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni (AENSI Publications, 2015)
City, like the human is renewing and changing in every period and time. Also during its lifetime, city had experienced many ups and downs and had been changed by the shift of political regime. Islam and the Islamic thoughts were one of the events which has changed the structure and the view of many cities either existing or newly established. As a result Islamic cities came into existence, influenced by the religion, with an independent identity, because of the unique spatial pattern which defines the sense and the spirit of that city. In course of time, changes continued to take place in the Islamic cities and different factors had effects on the structure of those cities and one of the most important factors was entering the western culture through the Islamic cities that changes everything resulting duality between the structure of the new cities and the old cities. This paper presents a brief proposal for renovation of Islamic city in order to preserve the Islamic identity.